2013
DOI: 10.1186/1471-2474-14-151
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of claims-based recurrent low back pain in a Canadian population: A secondary analysis of an administrative database

Abstract: BackgroundThere is a vast literature reporting that the point prevalence of low back pain (LBP) is high and increasing. It is also known that a large proportion of acute LBP episodes are recurrent within 12 months. However, few studies report the annual trends in the prevalence of recurrent LBP or describe these trends according to age and sex categories.MethodsWe conducted a retrospective cohort study involving 401 264 adults selected from the administrative database of physician claims for the province of Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 45 publications
1
39
0
1
Order By: Relevance
“…The total economic cost of LBP in Canada has been estimated at over 8 billion dollars per year [2], with a prevalence of compensation claims for LBP of approximately 38% in the working population [3]. Most concerning is the duration of work disability following sick leave for LBP, which contributes to staggering economic costs to health care, employers, employees, and society [4].…”
Section: Introductionmentioning
confidence: 99%
“…The total economic cost of LBP in Canada has been estimated at over 8 billion dollars per year [2], with a prevalence of compensation claims for LBP of approximately 38% in the working population [3]. Most concerning is the duration of work disability following sick leave for LBP, which contributes to staggering economic costs to health care, employers, employees, and society [4].…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] It is reported that more than half of patients complaining of low back pain experience diminishment in their working lives and daily activities and in Europe, this is the second most frequent cause of sick leaves. This places a great burden on both the health system and the economy.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] A great majority of patients presenting with low back pain complaints benefit from conservative and noninvasive modes of treatment that include bed rest, oral medications, corsets and physical therapy but one-fourth of these patients are likely to reappear at the hospital within the same year due to a relapse of the condition.Ten percent of such patients become chronic cases and 10%-15% ultimately need surgery. [1,3,[5][6][7] Of patients undergoing surgery, 20% go through another surgical procedure due to continued pain. [8] This situation has led patients to consider more effective and minimally invasive treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective population-based cohort study was prepared using medical administrative data extracted from the registries of the Régie de l'Assurance Maladie du Québec (RAMQ) (Beaudet et al, 2013). Analyses were performed on the RAMQ provincial physicians' claims database, which provided information on the patients' identification, the date of service and the primary diagnosis for each visit (four-digit ICD-9).…”
Section: Design and Data Sourcesmentioning
confidence: 99%
“…Prevalent claims-based recurrent LBP patients were selected if they had at least three identical LBP diagnoses in a period of 365 days (Beaudet et al, 2013). Prevalent claims-based recurrent LBP patients were selected if they had at least three identical LBP diagnoses in a period of 365 days (Beaudet et al, 2013).…”
Section: Study Populationmentioning
confidence: 99%